Size effect of carbon fiber-reinforced silicon carbide composites (C/C-SiC): Part 2 - tensile testing with alignment device. Issue 4 (April 2022) - Flauder, Stefan; Bombarda, Ilaria; D'Ambrosio, Roberto; Langhof, Nico; Lazzeri, Andrea; Krenkel, Walter; Schafföner, Stefan
Abstract: The appropriate assessment of mechanical properties is essential to design ceramic matrix composites. The size effect of strength plays a key role for the material understanding and the transfer from lab-scale samples to components. In order to investigate the size effect for carbon fiber-reinforced silicon carbon (C/C-SiC) under tensile load, a tensile testing with a minimum of deviation from the pure tensile loading is necessary. Hence, a hybrid edge/face-loading test device for self-alignment and centering of C/C-SiC tensile samples was developed, evaluated and proved to ensure pure tensile load. The mechanical analysis of more than 190 samples with two different cross-sections fabricated from the same material population revealed no significant difference in tensile strength. Although the volume under load was increased from 129 to 154 mm 3, the tensile strengths of 162 ± 7 and 164 ± 6 MPa did not change. These results are discussed regarding the weakest link and energetic size effect approaches.